European Journal of Phycology - European Journal of Phycology (Taylor & Francis, 2026)
The European Journal of Phycology is an important focus for the activities of algal researchers all over the world. The Editors-in-Chief are assisted by an international team of Associate Editors who are experts in the following fields: macroalgal ecology, microalgal ecology, physiology and biochemistry, cell biology, molecular biology, macroalgal and microalgal systematics, applied phycology and biotechnology. The European Journal of Phycology publishes papers on all aspects of algae, including cyanobacteria. Articles may be in the form of primary research papers and reviews of topical subjects.
FI 0.71
Q2
Keywords: Biological; Earth & Environmental Food Science; Ficología; Acuerdos transformativos; Transformative agreements; Cianobacterias; Macroalgas; Microalgas